An MRI review of acquired corpus callosum lesions. Issue 9 (21st February 2014) - Renard, Dimitri; Castelnovo, Giovanni; Campello, Chantal; Bouly, Stephane; Le Floch, Anne; Thouvenot, Eric; Waconge, Anne; Taieb, Guillaume
Abstract : Lesions of the corpus callosum (CC) are seen in a multitude of disorders including vascular diseases, metabolic disorders, tumours, demyelinating diseases, trauma and infections. In some diseases, CC involvement is typical and sometimes isolated, while in other diseases CC lesions are seen only occasionally in the presence of other typical extra-callosal abnormalities. In this review, we will mainly discuss the MRI characteristics of acquired lesions involving the CC. Identification of the origin of the CC lesion depends on the exact localisation of the lesion(s) inside the CC, presence of other lesions seen outside the CC, signal changes on different MRI sequences, evolution over time of the radiological abnormalities, history and clinical state of the patient, and other radiological and non-radiological examinations.